The effect of object familiarity on the perception of motion - Martín, Andrés (2015)
Humans are capable of picking up the invariance of an object’s physical speed regardless of the distance from which it is seen. This ability is known as speed constancy. Typically the studies of speed constancy focus on the spatiotemporal cues present in the stimulus. In this work we present a series of experiments that introduce the object’s familiarity in combination with other cues to study the speed constancy. The results of the first experiment show that human observers use said familiarity in the estimation of the physical speed of the objects. When distance cues are added to the stimulus, the results show that familiarity helps the system to achieve speed constancy. In the second experiment we remove the contextual cues and show the effect of familiarity on speed constancy. Finally, we propose that familiarity needs to be included in the analysis of speed constancy perhaps by considering the prototypical size of the objects.